2020
DOI: 10.3390/biom10091323
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Inhibits the Primary Nucleation of Amyloid-Beta Peptide: A Molecular Dynamics Study

Abstract: The amyloid plaques are a key hallmark of neurodegenerative diseases such as Alzheimer’s disease and Parkinson’s disease. Amyloidogenesis is a complex long-lasting multiphase process starting with the formation of nuclei of amyloid peptides: a process assigned as a primary nucleation. Curcumin (CU) is a well-known inhibitor of the aggregation of amyloid-beta (Aβ) peptides. Even more, CU is able to disintegrate preformed Aβ firbils and amyloid plaques. Here, we simulate by molecular dynamics the primary nucleat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 75 publications
2
21
0
1
Order By: Relevance
“…These discrepancies may be dependent on the software used and also the Aβ isoform, their energy levels and variation of many more experimental parameters. However, our studies and previous reports agreed that, among all these amino acids, Asp, Tyr, Ala, Lys and Thr play greater role for Aβ aggregation and that Cur/turmeric derivatives interacted with these amino acids more favorable [48], suggesting that these Cur/turmeric derivatives have critical roles in Aβ aggregation inhibition [47,49] (Figures 1-4, Table S4).…”
Section: Discussionsupporting
confidence: 81%
“…These discrepancies may be dependent on the software used and also the Aβ isoform, their energy levels and variation of many more experimental parameters. However, our studies and previous reports agreed that, among all these amino acids, Asp, Tyr, Ala, Lys and Thr play greater role for Aβ aggregation and that Cur/turmeric derivatives interacted with these amino acids more favorable [48], suggesting that these Cur/turmeric derivatives have critical roles in Aβ aggregation inhibition [47,49] (Figures 1-4, Table S4).…”
Section: Discussionsupporting
confidence: 81%
“…However, the anti‐amyloidogenic effects of curcumin are not well understood. Molecular dynamics simulations revealed that curcumin could affect both the process of primary nucleation and elongation of amyloid fibrils 74,75 . At the first step of amyloid formation, curcumin and curcumin derivatives intercalate among the Aβ chains and bind tightly by hydrogen bonds and hydrophobic and cation interactions, leading to bigger primary nuclei, being less flexible and more disordered amyloid structures 75 .…”
Section: Effects Of Curcumin On Amyloid Aggregationmentioning
confidence: 99%
“…Molecular dynamics simulations revealed that curcumin could affect both the process of primary nucleation and elongation of amyloid fibrils 74,75 . At the first step of amyloid formation, curcumin and curcumin derivatives intercalate among the Aβ chains and bind tightly by hydrogen bonds and hydrophobic and cation interactions, leading to bigger primary nuclei, being less flexible and more disordered amyloid structures 75 . Moreover, it can also decrease the number of β‐strands and increase the distance between amino acids responsible for aggregations 76 .…”
Section: Effects Of Curcumin On Amyloid Aggregationmentioning
confidence: 99%
“…The effects of CU on the stability of dimers and protofibrils have been simulated and the mechanisms of interactions have been investigated at atomistic level [ 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Recently, we simulated the primary nucleation process of 12 Aβ peptides and studied the effects of CU and FA on the process [ 48 ]. We found that CU intercalates among the peptide chains, binds tightly to Aβ by hydrogen bonds, hydrophobic, π–π, and cation–π interactions and prevents the formation of a compact primary nucleus.…”
Section: Introductionmentioning
confidence: 99%